Mechanism of yield compensation in some accession of cowpea grown at different plant densities and environments - Odesina, I.S. (2024)
Grain yield of cowpea [Vigna unguiculata (L.) Walp.] in Nigerian savannas are low despite the cultivation of improved accessions. Amongst a host of production constraints, missing plant stand has been suggested to contribute to yield loss in cowpea. Gap-filling could be used as alternative to mitigate yield losses caused by stand reduction. This study, which was carried out in 2020, was aimed at investigating the mechanism of yield compensation in some accessions of cowpea in two savannah agro-ecologies at Minjibir and Shika in Northern Nigeria. The randomised complete block design in a split-plot arrangement in three replicates was used. The main plot consisted of four plant densities (33,333, 66,666, 99,999 and 133,333 plants ha-1) while the sub-plots consisted of six cowpea accessions (DANILA, IT08K-150-27, IT89KD-288, IT93K-452-1, IT98K-205-8 and IT99K-573-1-1). Results showed that plant density and environment affected grain yield. Total grain yield increased with increasing plant density. Generally, total grain yield was higher at Minjibir than at Shika. The highest total grain yield of 1,793.3 kg ha-1 was observed in the accession DANILA at 99,999 plants ha-1, while the lowest(1,100 kg ha-1) was observed in the accession IT98K-205-8 at 33, 333 plants ha-1. Stand count at harvest, leaf area index and intercepted photosynthetically active radiation and pod weight were positively correlated with total grain yield at both locations, suggesting that these traits could be considered for cowpea improvement. Cowpea growers and breeders could consider erect accessions (IT93K-452-1 and IT98K-205-8) and semi-erect accessions (IT99K-573-1-1 and IT08K-150-27) for cultivation at 133,333 plants ha-1 and prostrate accessions (IT89KD-288 and DANILA) at 99,999 plants ha-1 at Minjibir. The accession IT93K-452-1-1, IT98-205-8, IT99K-573-1-1 and IT08K-150-27 could be considered for cultivation at Shika, irrespective of plant density.